Composite al-plastic film for battery based on electron beam curing and preparation method thereof
By introducing a gradient interfacial adhesive layer into the composite aluminum-plastic film and employing electron beam curing technology, the problem of insufficient stress release capability of the composite aluminum-plastic film in improving its resistance to electrolytes and humid heat bonding stability has been solved, achieving a balance between durable bonding and cold drawing deep forming.
Patent Information
- Application Number
- CN202611209877.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-11-06
AI Technical Summary
While existing composite aluminum-plastic films improve resistance to electrolytes and wet heat bonding stability, they tend to weaken the stress release capability in cold drawing and deep forming, making it difficult to balance durable interfacial bonding and molding adaptability.
The composite aluminum-plastic film structure based on electron beam curing includes a biaxially oriented polyamide film, a gradient interfacial adhesive layer, an aluminum foil, and a heat-sealing layer. The gradient interfacial adhesive layer is composed of a first polycarbonate polyurethane acrylate containing carboxyl groups and a second polycarbonate polyurethane acrylate with bifunctionality, which forms a moderately cross-linked network structure through electron beam irradiation.
It improves the resistance of the adhesive layer to electrolyte and damp heat aging, while maintaining the adaptability to cold drawing and deep forming, and avoids the imbalance between durability and formability caused by single uniform high cross-linking or low cross-linking.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery packaging materials technology, and in particular to a composite aluminum-plastic film for batteries based on electron beam curing and its preparation method. Background Technology
[0002] Battery composite aluminum-plastic films typically consist of an outer polyamide film, an aluminum foil barrier layer, an inner heat-sealing layer, and an interlayer adhesive or coating layer. Stable interlayer bonding must be maintained under conditions of electrolyte immersion, damp heat aging, and cold deep forming. Existing technologies have focused on improvements to aluminum foil surface corrosion protection, polyurethane adhesives, and radiation-cured composite adhesives.
[0003] Patent CN102602597B discloses an aluminum-plastic packaging film for lithium-ion batteries and its manufacturing method, which improves electrolyte corrosion resistance and formability by coating the aluminum foil surface with a corrosion-resistant coating layer. Patent CN101914363B discloses a polyurethane adhesive for lithium battery packaging films and a lithium battery packaging film, using a modified polyurethane adhesive to composite aluminum foil and a heat-sealing layer to improve peel strength under working conditions. Patent CN114921212B discloses an aluminum-plastic film adhesive, which uses a modified polyester polyol and a curing agent to form an adhesive system to improve adhesion, water resistance, and deep-diving resistance. Furthermore, patent CN110387208B discloses an electron beam-cured composite adhesive, which can be used for flexible packaging composite films and shortens curing and ripening time.
[0004] However, the aforementioned solutions mostly focus on improving the aluminum foil anti-corrosion layer, the composition of the single-sided adhesive, the uniform adhesive layer, or the efficiency of ordinary flexible packaging composites. In composite aluminum-plastic films for batteries, while increasing the overall cross-linking degree of the adhesive layer is beneficial for maintaining adhesion after electrolyte and humid heat conditions, it can easily reduce the stress buffering capacity during cold drawing and deep forming. Conversely, reducing the cross-linking degree can easily cause the adhesive layer to swell, decrease cohesion, or peel off at the interface under high-temperature electrolyte or humid heat environments. Therefore, a composite aluminum-plastic film and its preparation method that can balance durable interfacial adhesion and adaptability to cold drawing and deep forming are still needed. Summary of the Invention
[0005] In view of this, the purpose of this invention is to propose a composite aluminum-plastic film for batteries based on electron beam curing and its preparation method, so as to solve the problem that the existing composite aluminum-plastic film interface adhesive layer easily weakens the stress release ability in cold drawing deep forming when improving the electrolyte resistance and wet heat bonding stability, and it is difficult to take into account both durable bonding and molding adaptability.
[0006] To achieve the above objectives, the present invention provides a composite aluminum-plastic film for batteries based on electron beam curing, comprising a biaxially oriented polyamide film, a gradient interface adhesive layer, an aluminum foil, a bonding layer, and a heat-sealing layer arranged sequentially. The gradient interface adhesive layer comprises a metal-side coating near the aluminum foil and a resin-side coating near the biaxially oriented polyamide film; the metal-side coating contains a first polycarbonate polyurethane acrylate containing carboxyl groups and partially end-capped with acrylic acid, and a bifunctional second polycarbonate polyurethane acrylate; the resin-side coating contains the second polycarbonate polyurethane acrylate, the first polycarbonate polyurethane acrylate, and tricyclodecanedimethyl diacrylate; based on the percentage of insoluble matter after immersion in acetone at 23°C for 48 hours to the initial dry mass, the gel rate of the metal-side coating is 45%-70%, and the gel rate of the resin-side coating is 75%-95%.
[0007] Preferably, the first polycarbonate polyurethane acrylate is obtained by reacting polycarbonate diol, 2,2-dimethylolbutyric acid and isophorone diisocyanate, and then capping with hydroxyethyl acrylate and n-butanol. In preparing the first polycarbonate polyurethane acrylate, the mass ratio of polycarbonate diol, 2,2-dimethylolbutyric acid, isophorone diisocyanate, hydroxyethyl acrylate and n-butanol is 1000.00:51.86:389.01:44.13:31.13, and hydroxyethyl acrylate and n-butanol are added for capping when the isocyanate group content is 2.35%, and the reaction continues until the residual isocyanate group mass content is not higher than 0.05%.
[0008] Preferably, the second polycarbonate polyurethane acrylate is obtained by reacting polycarbonate diol and isophorone diisocyanate, followed by end-capping with hydroxyethyl acrylate; when preparing the second polycarbonate polyurethane acrylate, the mass ratio of polycarbonate diol, isophorone diisocyanate and hydroxyethyl acrylate is 1000.00:444.58:232.24, and hydroxyethyl acrylate is added for end-capping when the isocyanate group content is 5.85%, and the reaction continues until the residual isocyanate group mass content is not higher than 0.05%.
[0009] Preferably, the metal side coating is formed of 54.0 parts by mass of a first polycarbonate polyurethane acrylate, 45.8 parts by mass of a second polycarbonate polyurethane acrylate, and 0.2 parts by mass of a leveling agent, with a total non-volatile content of 100 parts by mass.
[0010] Preferably, the total amount of non-volatile components in the resin side coating is 100 parts by mass, and the resin side coating is formed from 73.8 parts by mass of second polycarbonate polyurethane acrylate, 18.0 parts by mass of first polycarbonate polyurethane acrylate, 8.0 parts by mass of tricyclodecanediethanol diacrylate and 0.2 parts by mass of leveling agent.
[0011] Preferably, the thickness of the biaxially oriented polyamide film is 25.0 μm, the thickness of the aluminum foil is 40.0 μm, the bonding layer is a maleic anhydride-grafted polypropylene layer with a thickness of 5.0 μm, and the heat-sealing layer is a cast polypropylene layer with a thickness of 65.0 μm.
[0012] Preferably, the aluminum foil has a chromium-free conversion film on the side facing the gradient interface adhesive layer, and the weight gain of the chromium-free conversion film is 15 mg / m³. 2 .
[0013] Preferably, the non-volatile content of the gradient interface adhesive layer is 4.50 g / m³. 2 .
[0014] Preferably, the gradient interface adhesive layer is formed by electron beam curing of a metal-side coating first formed on the surface of the aluminum foil and a resin-side coating subsequently formed on the metal-side coating, and the electron beam is irradiated from one side of the biaxially oriented polyamide film.
[0015] Furthermore, the present invention also provides a method for preparing a composite aluminum-plastic film for batteries based on electron beam curing, characterized by comprising the following steps: preparing a first polycarbonate polyurethane acrylate and a second polycarbonate polyurethane acrylate; preparing a metal side coating liquid and a resin side coating liquid; first coating the aluminum foil to be coated with the metal side coating liquid, so that the residual solvent of the first coating film is 8.6%-17.2%; after the first coating film leaves the flash evaporation section, coating the resin side coating liquid after 1.8-4.5s, and then drying them together; after the biaxially oriented polyamide film and the resin side coating film are composited, electron beam irradiation is performed from one side of the biaxially oriented polyamide film, the electron beam accelerating voltage is 150-170keV, and the planar absorbed dose of the adhesive layer is 28.0-36.0kGy.
[0016] Preferably, the metal side coating liquid is prepared from 900.00 parts by weight of a first polycarbonate polyurethane acrylate solution, 654.29 parts by weight of a second polycarbonate polyurethane acrylate solution, 2.00 parts by weight of a leveling agent, 220.07 parts by weight of ethyl acetate and 146.72 parts by weight of methyl ethyl ketone; the resin side coating liquid is prepared from 1054.29 parts by weight of a second polycarbonate polyurethane acrylate solution, 300.00 parts by weight of a first polycarbonate polyurethane acrylate solution, 80.00 parts by weight of tricyclodecanediethanol diacrylate, 2.00 parts by weight of a leveling agent, 292.07 parts by weight of ethyl acetate and 194.72 parts by weight of methyl ethyl ketone.
[0017] Preferably, the aluminum foil surface to be coated is preheated to 45°C before coating, and the wet coating amount of the metal side coating liquid is 3.27 g / m². 2The flash evaporation temperature was 58℃; the wet coating amount of the resin side coating liquid was 5.38 g / m². 2 During the co-drying process, the product passes through three drying zones at 55℃, 72℃, and 85℃ in sequence, with residence times of 20s, 30s, and 40s, respectively. The composite roller temperature is 62℃, the average contact pressure is 0.35MPa, and the production line speed is 12.0m / min.
[0018] Preferably, the oxygen content in the irradiation chamber is 180 mg / kg during electron beam irradiation, and the temperature of the composite film entering the irradiation area is 45°C. After electron beam irradiation, the composite film is passed through a 30°C cooling roller and wound up, and placed at 25°C for 24 hours to obtain the electron beam-cured composite aluminum-plastic film for batteries.
[0019] The beneficial effects of this invention are:
[0020] This invention forms a gradient interfacial adhesive layer between an aluminum foil and a biaxially oriented polyamide film, consisting of a metal-side coating and a resin-side coating. The side closest to the aluminum foil uses a first polycarbonate polyurethane acrylate containing carboxyl groups and partially capped with acrylic acid. This facilitates the distribution of carboxyl groups along the polyurethane matrix close to the aluminum foil surface, improving the interfacial bonding stability with the aluminum foil conversion film. The partial acrylic acid capping allows for moderate cross-linking on this side after electron beam irradiation, maintaining cohesion while retaining a certain degree of stress release capability.
[0021] A bifunctional second polycarbonate polyurethane acrylate is introduced near the polyamide film side, along with irradiable reactive components such as tricyclodecanediethanol diacrylate, giving the resin-side coating a high reactive functional density. After electron beam curing, the resin side can form a high gel state, which helps improve the adhesive layer's resistance to electrolyte swelling and humid heat aging, and reduces peel strength decay under long-term use conditions.
[0022] This invention achieves limited interdiffusion and incomplete homogenization between the two coating layers by first applying a metal-side coating liquid, controlling the flash evaporation state of the first coating film and the interval between the two coatings, and then applying a resin-side coating liquid and drying them together. Combined with electron beam irradiation from the polyamide film side, a network structure transitioning from a moderate gel state on the metal side to a higher gel state on the resin side can be formed in the thickness direction. This structure is beneficial for simultaneously improving initial adhesion, electrolyte retention, peel stability after humid heat, and adaptability to cold-drawing deep forming, avoiding the imbalance between durability and formability caused by a single uniform highly cross-linked or low-cross-linked adhesive layer. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0024] The aliphatic copolymer polycarbonate diol used in the specific implementation method was purchased from Asahi Kasei Corporation, trade name DURANOL T5651, with a number average molecular weight of 1000 and a hydroxyl value of 112 mgKOH / g; 2,2-dimethylolbutyric acid was purchased from Sigma-Aldrich, catalog number 470627, with a purity of 98%; tricyclodecanediethanol diacrylate was purchased from Arkema Sartamomer, model SR833 S, with a functionality of 2; bismuth neodecanoate catalyst was purchased from Borchers, model Borchi Kat 315 EU, which is a solvent-free bismuth neodecanoate catalyst; leveling agent was purchased from BYK, model BYK-361 N, which is a solvent-free polyacrylate surface additive; the aluminum foil used was 8021-O soft aluminum foil with a thickness of 40.0 μm; the biaxially oriented polyamide film used was PHA type lithium battery packaging biaxially oriented polyamide film from Xiamen Changsu Industrial Co., Ltd., with a thickness of 25.0 μm.
[0025] Example 1:
[0026] 1. Preparation of a first polycarbonate polyurethane acrylate containing carboxyl groups and partially acrylic acid-terminated.
[0027] 1000.00 g of polycarbonate diol was added to a reactor equipped with a mechanical stirrer, thermometer, condenser, nitrogen inlet, and sampling port. The material was heated to 95°C and dehydrated for 60 min under a gauge pressure of -0.085 MPa. In another container equipped with a condenser, 51.86 g of 2,2-dimethylolbutyric acid (DMA) and 260.00 g of acetone (based on the effective component) were added. The mixture was stirred at 45°C and 500 rpm for 30 min to obtain a 16.63% DMA solution. The polycarbonate diol in the reactor was cooled to 45°C, and 450.82 g of ethyl acetate, 300.54 g of butanone, the above DMA / acetone solution, and 0.46 g of bismuth neodecanoate catalyst were added sequentially. The mixture was stirred at 45°C and 400 rpm for 20 min. The system was heated to 50°C, and 389.01 g of isophorone diisocyanate was added within 60 min. During the addition, the temperature of the reaction system was controlled at 50-55°C. After the addition was completed, the reaction system was heated to 58°C and reacted under reflux conditions until the isocyanate group content was determined to be 2.35% by the di-n-butylamine back titration method. Then, the end-capping process was initiated. 44.13 g of hydroxyethyl acrylate, 31.13 g of n-butanol, and 0.45 g of hydroquinone monomethyl ether were mixed and added to the reactor at 50°C within 30 min. After the addition was completed, the reaction was continued at 58°C. The residual isocyanate group mass content was determined by the di-n-butylamine back titration method. When it was not higher than 0.05%, the reaction was terminated. The reactants were cooled to 30°C and filtered through a 20 μm filter to obtain the first polycarbonate polyurethane acrylate solution.
[0028] 2. Preparation of bifunctional second polycarbonate polyurethane acrylate
[0029] Add 1000.00 g of polycarbonate diol to another reactor, heat the material to 95°C, dehydrate for 60 min under a gauge pressure of -0.085 MPa, cool the reactants to 50°C, and add 431.44 g of ethyl acetate, 287.63 g of butanone, and 0.50 g of bismuth neodecanoate catalyst sequentially. Stir at 400 rpm for 20 min, and add 444.58 g of isophorone diisocyanate over 60 min at 55°C. After the addition is complete, heat to 75°C and react. When the isocyanate group content was determined to be 5.85% by the di-n-butylamine back titration method, the end-capping process was initiated. The reaction system was cooled to 50°C, and 232.24g of hydroxyethyl acrylate and 0.50g of hydroquinone monomethyl ether were mixed and added to the reaction vessel within 45 minutes. After the addition was complete, the reaction was carried out at 60°C. The reaction was terminated when the residual isocyanate group mass content was not higher than 0.05%. The reactants were cooled to 30°C and filtered through a 20μm filter to obtain the second polycarbonate polyurethane acrylate solution.
[0030] 3. Preparation of metal side coating liquid
[0031] Add 900.00g of the first polycarbonate polyurethane acrylate solution, 654.29g of the second polycarbonate polyurethane acrylate solution, 2.00g of leveling agent, 220.07g of ethyl acetate and 146.72g of methyl ethyl ketone to the mixing tank in sequence, stir at 25℃ and 300rpm for 30min, and filter through a 20μm filter to obtain the metal side coating liquid;
[0032] 4. Preparation of resin side coating solution
[0033] Add 1054.29g of the second polycarbonate polyurethane acrylate solution, 300.00g of the first polycarbonate polyurethane acrylate solution, 80.00g of tricyclodecanediethanol diacrylate, 2.00g of leveling agent, 292.07g of ethyl acetate and 194.72g of butanone to another mixing tank in sequence. Stir at 25℃ and 300rpm for 30min. Filter through a 20μm filter to obtain the resin side coating solution.
[0034] 5. Coating of the gradient interface adhesive layer
[0035] A pre-formed inner layer structure of aluminum foil roll is used as the coating substrate. The roll comprises, in sequence, a 65.0 μm cast polypropylene heat-sealing layer, a 5.0 μm maleic anhydride-grafted polypropylene bonding layer, and a 40.0 μm aluminum foil. The aluminum foil surface to be coated has a conventional chromium-free conversion film with a conversion film weight gain of 15 mg / m³. 2 The aluminum foil to be coated is preheated to 45°C, and the metal side coating liquid is applied using the first gravure coating unit, with a wet coating amount of 3.27 g / m².2 The first coating passes through a flash evaporation section at 58°C and remains for 28 seconds. After leaving the flash evaporation section, the first coating passes through a second gravure coating unit for 3.0 seconds before entering the second gravure coating unit. The second gravure coating unit then applies the resin side coating solution, with a wet coating amount of 5.38 g / m². 2 After two coatings, the roll material is passed through three drying zones at 55℃, 72℃ and 85℃ in sequence, with dwell times of 20s, 30s and 40s respectively.
[0036] 6. Resin film lamination and electron beam curing
[0037] A 25.0 μm thick biaxially oriented polyamide film was used as the outer resin film. The biaxially oriented polyamide film was then laminated with the resin side coating film. The lamination roller temperature was 62℃, the average contact pressure was 0.35 MPa, and the production line speed was 12.0 m / min. After lamination, the biaxially oriented polyamide film was subjected to one electron beam irradiation. The electron beam accelerating voltage was 160 keV, the planar absorbed dose of the adhesive layer was 32.0 kGy, the oxygen content in the irradiation chamber was 180 mg / kg, and the temperature of the composite film when it entered the irradiation zone was 45℃. The planar absorbed dose of the adhesive layer was calibrated using a dosimeter from the same batch. After electron beam irradiation, the composite film was passed through a 30℃ cooling roller and wound up. It was then placed at 25℃ for 24 hours to obtain a battery composite aluminum-plastic film based on electron beam curing.
[0038] Example 2:
[0039] The difference between Example 2 and Example 1 is that the residence time of the first coating in the 58°C flash evaporation section is adjusted to 35s, so that the residual solvent of the first coating is 8.6%, and the first coating enters the second gravure coating unit after 4.5s after leaving the flash evaporation section; the electron beam accelerating voltage is 160keV, the planar absorbed dose of the adhesive layer is 32.0kGy, and the other conditions are the same as in Example 1.
[0040] Example 3:
[0041] The difference between Example 3 and Example 1 is that the residence time of the first coating in the 58°C flash evaporation section is adjusted to 21s, so that the residual solvent of the first coating is 17.2%, and the first coating enters the second gravure coating unit 1.8s after leaving the flash evaporation section; the electron beam accelerating voltage is 160keV, the planar absorbed dose of the adhesive layer is 32.0kGy, and the other conditions are the same as in Example 1.
[0042] Example 4:
[0043] The difference between Example 4 and Example 1 is that the electron beam accelerating voltage is 150 keV, the planar absorbed dose of the adhesive layer is 28.0 kGy, and the other conditions are the same as in Example 1.
[0044] Example 5:
[0045] The difference between Example 5 and Example 1 is that the electron beam accelerating voltage is 170 keV and the planar absorbed dose of the adhesive layer is 36.0 kGy, while the other conditions are the same as in Example 1.
[0046] Comparative Example 1:
[0047] Comparative Example 1 uses a uniform single-layer interfacial adhesive layer. Based on 1000.00g of non-volatile matter, 526.67g of a first polycarbonate polyurethane acrylate solution, 902.86g of a second polycarbonate polyurethane acrylate solution, 50.00g of tricyclodecanediethanol diacrylate, 2.00g of leveling agent, 264.93g of ethyl acetate, and 176.62g of butanone were added sequentially to a mixing tank. The mixture was stirred at 25°C and 300rpm for 30 minutes, and then filtered through a 20μm filter to obtain a single-layer coating with a non-volatile matter content of 52.0%. The single-layer coating was then subjected to a process at 8.65g / m³. 2 The wet coating was applied to the aluminum foil surface in one pass, and then sequentially passed through three drying zones at 55°C, 72°C, and 85°C, with dwell times of 20s, 30s, and 40s, respectively. The non-volatile coating amount after drying was 4.50 g / m², followed by resin film lamination and electron beam curing according to the conditions of Example 1.
[0048] Comparative Example 2:
[0049] Comparative Example 2: Preparation of a carboxyl-free first polycarbonate polyurethane acrylate. 1000.00 g of polycarbonate diol was added to a reactor, and the material was heated to 95°C and dehydrated for 60 min under a gauge pressure of -0.085 MPa. In another container equipped with a condenser, 31.54 g of 1,4-butanediol and 260.00 g of acetone were added, and the mixture was stirred at 45°C and 500 rpm for 30 min. The polycarbonate diol in the reactor was cooled to 45°C, and 442.69 g of ethyl acetate, 295.12 g of butanone, the above-mentioned 1,4-butanediol-acetone solution, and 0.46 g of bismuth neodecanoate catalyst were added sequentially. The mixture was stirred at 45°C and 400 rpm for 20 min. The subsequent addition amounts, methods, reaction temperatures, isocyanate group control points, and the amounts of hydroxyethyl acrylate, n-butanol, and hydroquinone monomethyl ether were all the same as in step 1 of Example 1, yielding a carboxyl-free first polycarbonate polyurethane acrylate solution with a non-volatile content of 60.0%. This solution was used to replace the first polycarbonate polyurethane acrylate solution in the metal side coating and resin side coating solutions of Example 1 by an equal mass, with all other conditions remaining the same as in Example 1.
[0050] Comparative Example 3:
[0051] Comparative Example 3 involved the addition of carboxyl groups as free small molecules. 1608.23 g of the carboxyl-free first polycarbonate polyurethane acrylate solution obtained in Comparative Example 2 was taken, of which 964.94 g was non-volatile. 34.22 g of 2,2-dimethylolbutyric acid and 171.55 g of acetone were stirred at 45°C and 500 rpm for 30 min, then added to the aforementioned solution. Next, 0.84 g of tricyclodecanediethanol diacrylate was added, and the mixture was stirred at 45°C and 300 rpm for 30 min. 148.17 g of solvent was removed at 45°C and a gauge pressure of -0.060 MPa, yielding a first-component solution with a non-volatile content of 60.0% by mass. The theoretical acid value of this solution was 12.95 mg KOH / g, and the theoretical carbon-carbon double bond content was 0.2507 mmol / g. The first polycarbonate polyurethane acrylate solution in the metal side coating liquid and resin side coating liquid of Example 1 was replaced with this solution by the same mass, and the other conditions were the same as in Example 1.
[0052] Comparative Example 4:
[0053] In Comparative Example 4, all the terminal isocyanate groups of the first polycarbonate polyurethane acrylate were capped with n-butanol. Hydroxyethyl acrylate was not added during the preparation of the first polycarbonate polyurethane acrylate; instead, 59.30 g of n-butanol was added. The amounts of ethyl acetate and butanone were adjusted to 444.43 g and 296.29 g, respectively, so that the non-volatile content of the resulting solution was 60.0%. The remaining preparation and compounding conditions were the same as in Example 1.
[0054] Comparative Example 5:
[0055] In Comparative Example 5, all the terminal isocyanate groups of the first polycarbonate polyurethane acrylate were capped with hydroxyethyl acrylate. Instead of adding n-butanol during the preparation of the first polycarbonate polyurethane acrylate, 92.90 g of hydroxyethyl acrylate was added; the amounts of ethyl acetate and butanone were adjusted to 457.87 g and 305.25 g, respectively, so that the non-volatile content of the resulting solution was 60.0% by mass. The remaining preparation and compounding conditions were the same as in Example 1.
[0056] Comparative Example 6:
[0057] The difference between Comparative Example 6 and Example 1 is that the residence time of the first coating in the 58°C flash evaporation section is adjusted to 60s, so that the residual solvent of the first coating is 3.0%. After the first coating leaves the flash evaporation section, it enters the second gravure coating unit after 3.0s. The other conditions are the same as in Example 1.
[0058] Comparative Example 7:
[0059] The difference between Comparative Example 7 and Example 1 is that the residence time of the first coating in the flash evaporation section at 58°C was adjusted to 12s, so that the residual solvent of the first coating was 24.0%. After the first coating left the flash evaporation section, it entered the second gravure coating unit after 3.0s. The other conditions were the same as in Example 1.
[0060] Comparative Example 8:
[0061] The difference between Comparative Example 8 and Example 1 is that: first, a resin side coating liquid is applied to the surface of the aluminum foil with a wet coating amount of 5.38 g / m2, so that the residual solvent of the first coating film is 12.5%. After 3.0 s, a metal side coating liquid is applied with a wet coating amount of 3.27 g / m2. Then, they are dried, laminated and cured with electron beam. The other conditions are the same as those in Example 1.
[0062] Comparative Example 9:
[0063] The difference between Comparative Example 9 and Example 1 is that the electron beam accelerating voltage is 160 keV, the planar absorbed dose of the adhesive layer is 20.0 kGy, and the other conditions are the same as those in Example 1.
[0064] Performance testing
[0065] Conditioning: Except for the residual solvent and gelation rate tests, the other samples were placed in an environment of 23±2℃ and 50±10% relative humidity for 24 hours before testing, in accordance with GB / T 2918-2018.
[0066] Residual solvent: The coating at the corresponding process node is obtained on the aluminum foil witness sheet that is running synchronously with the roll material. Weigh the mass m0 of the uncoated witness sheet, the total mass m1 of the witness sheet and coating at the time of sampling, and the total mass m2 after vacuum drying at 105℃ to constant weight. Calculate the residual solvent according to the formula: residual solvent = (m1-m2) / (m1-m0)×100%. Take the average value of 3 witness sheets in each group.
[0067] Gel content: The metal side coating liquid and the resin side coating liquid were coated onto the release polyester film respectively, with a non-volatile coating amount of 5.0 g / m². 2 After drying, a 25.0 μm biaxially oriented polyamide film was applied, and the film was irradiated with an electron beam according to the accelerating voltage and absorbed dose of the corresponding embodiment or comparative example. The initial dry mass m3 of the cured film was weighed and immersed in acetone at 23°C for 48 h, with the acetone being replaced after 24 h. After removal, the film was vacuum dried at 60°C to constant weight, and the mass m4 was weighed. The gel rate was calculated as m4 / m3 × 100%, and the average value of 3 samples in each group was taken.
[0068] Initial peel force: The peel test between the biaxially oriented polyamide film and the aluminum foil was conducted in accordance with GB / T 8808-1988. The sample width was 15 mm, the peel speed was 100±10 mm / min, and 5 samples were tested in each group and the average value was taken.
[0069] Electrolyte resistance: The electrolyte consists of ethylene carbonate, diethyl carbonate, and dimethyl carbonate in a 1:1:1 molar ratio, with a lithium hexafluorophosphate concentration of 1.0 mol / L and a free acid content not exceeding 50 mg / kg. The sample is completely immersed in the electrolyte in a sealed container and placed at 85±2℃ for 24 h and 168 h, respectively. After removal, the surface electrolyte is wiped off, and the sample is tested within 30 min according to the initial peel force test conditions. The peel force retention rate after 168 h is calculated.
[0070] Peel strength after damp heat: The sample was placed in an environment of 60±2℃ and 90±5% relative humidity for 72 hours, and then placed at 23±2℃ for 2 hours. The test was carried out according to the test conditions of the initial peel strength. Five samples were tested in each group and the average value was taken.
[0071] Cold drawing performance: Referring to the drawing test method of T / CIAPS 0005-2018, the standard drawing die and 130mm×240mm specimens were used, and the forming air pressure was 0.20MPa. The drawing depth increased in increments of 0.2mm, and the next higher depth without pinholes, cracks or delamination was taken as the maximum defect-free drawing depth; another 20 specimens were drawn to a depth of 6.0mm, and the pass rate was calculated.
[0072] Table 1 Process Control and Gelation Rate
[0073]
[0074] Table 2. Peeling, durability and cold drawing performance
[0075]
[0076] As shown in Tables 1-2, the gelation rates of the aluminum foil-side witness films in Examples 1-5 were all between 45% and 70%, and the gelation rates of the polyamide film-side witness films were all between 75% and 95%, while maintaining high initial peel strength, electrolyte peel strength, and cold drawing depth performance. Example 4 used a lower absorbed dosage, resulting in a higher maximum defect-free drawing depth, but its peel strength retention rate after 168 hours in the electrolyte was lower than that of Examples 1, 2, and 5. Example 5 used a higher absorbed dosage, resulting in higher peel strength after electrolyte and humid heat treatment, but its maximum defect-free drawing depth was slightly lower, indicating that a higher gelation rate is not necessarily better, and there is a balance between the stress release capability on the metal side and the swelling resistance on the resin side.
[0077] Comparative Example 1 uses a uniform single-layer coating. The witnessed film gel rate is 87.0% on both the aluminum foil side and the polyamide film side. The peel force retention rate after 168 hours in the electrolyte is 71.2%, and the maximum defect-free drawing depth is 5.4 mm. This indicates that under the same total non-volatile coating amount, a uniform high gel state is difficult to simultaneously achieve both long-term electrolyte resistance and cold drawing performance.
[0078] Comparative Example 2, which did not introduce carboxyl groups into the polyurethane backbone, showed a decrease in both initial peel strength and peel strength after aging. Comparative Example 3 adjusted the acid value and carbon-carbon double bond content to be close to those of Example 1, but the carboxyl groups existed as free small molecules, resulting in a higher initial peel strength than Comparative Example 2, while the peel strength retention rate after 168 hours in the electrolyte was only 60.6%. These results indicate that the bonding state between the carboxyl groups and the main structure of the first polycarbonate polyurethane acrylate has an impact on long-term interfacial stability.
[0079] Comparative Example 4, using a first polycarbonate polyurethane acrylate without acrylic end-capping, showed a reduced gelation rate of 32.7% in the witnessed film on the aluminum foil side. Although its cold drawing performance was good, the peel strength retention rate after 168 hours in the electrolyte solution was significantly lower. Comparative Example 5, using a first polycarbonate polyurethane acrylate entirely end-capped with hydroxyethyl acrylate, saw its witnessed film gelation rate increase to 74.6%. It exhibited good initial peel strength and electrolyte resistance, but the maximum defect-free drawing depth decreased to 5.0 mm. These results indicate that the reactive functional density of the first polycarbonate polyurethane acrylate needs to be controlled within a range that balances network fixation and stress release.
[0080] In Comparative Example 6, the residual solvent in the first coating was too low, resulting in insufficient interdiffusion between the two coatings. In Comparative Example 7, the residual solvent in the first coating was too high, leading to increased re-dissolution of the first coating by the second coating solution and an increase in the final residual solvent. Both examples showed lower peel strength retention and cold drawing performance after 168 hours in the electrolyte compared to Examples 1-3. In Comparative Example 8, after changing the coating sequence, a higher gel state formed on the side closer to the aluminum foil, reducing the 6.0mm drawing depth pass rate to 35%. In Comparative Example 9, the absorbed dose was insufficient, resulting in low gel rates for both witness films and decreased long-term electrolyte resistance. These results collectively indicate that the differences in the thickness direction network formed by the synergistic effects of coating composition, coating sequence, first coating state, contact time, and electron beam curing conditions are beneficial for improving the overall durability and molding adaptability of composite aluminum-plastic films.
[0081] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.
Claims
1. An electron beam-cured composite lamination film for a battery, characterized by comprising: The material comprises, in sequence, a biaxially oriented polyamide film, a gradient interfacial adhesive layer, an aluminum foil, a bonding layer, and a heat-sealing layer. The gradient interfacial adhesive layer includes a metal-side coating near the aluminum foil and a resin-side coating near the biaxially oriented polyamide film. The metal-side coating contains a first polycarbonate polyurethane acrylate containing carboxyl groups and partially end-capped with acrylic acid, and a bifunctional second polycarbonate polyurethane acrylate. The resin-side coating contains the second polycarbonate polyurethane acrylate, the first polycarbonate polyurethane acrylate, and tricyclodecanediethanol diacrylate. Based on the percentage of insoluble matter after immersion in acetone at 23°C for 48 hours to the initial dry mass, the gel rate of the metal-side coating is 45%-70%, and the gel rate of the resin-side coating is 75%-95%.
2. The electron beam-cured based composite lamination film for a battery according to claim 1, characterized by, The first polycarbonate polyurethane acrylate is obtained by reacting polycarbonate diol, 2,2-dimethylolbutyric acid and isophorone diisocyanate, followed by end-capping with hydroxyethyl acrylate and n-butanol. In preparing the first polycarbonate polyurethane acrylate, the mass ratio of polycarbonate diol, 2,2-dimethylolbutyric acid, isophorone diisocyanate, hydroxyethyl acrylate and n-butanol is 1000.00:51.86:389.01:44.13:31.
13. Hydroxyethyl acrylate and n-butanol are added for end-capping when the isocyanate group content is 2.35%, and the reaction continues until the residual isocyanate group mass content is no higher than 0.05%.
3. The electron beam-cured based composite lamination film for battery of claim 1, wherein, The second polycarbonate polyurethane acrylate is obtained by reacting polycarbonate diol and isophorone diisocyanate, followed by end-capping with hydroxyethyl acrylate. In preparing the second polycarbonate polyurethane acrylate, the mass ratio of polycarbonate diol, isophorone diisocyanate, and hydroxyethyl acrylate is 1000.00:444.58:232.
24. Hydroxyethyl acrylate is added for end-capping when the isocyanate group content is 5.85%, and the reaction continues until the residual isocyanate group mass content is no higher than 0.05%.
4. The electron beam-cured based composite lamination film for battery of claim 1, wherein, The metal side coating is formed of 54.0 parts by mass of a first polycarbonate polyurethane acrylate, 45.8 parts by mass of a second polycarbonate polyurethane acrylate, and 0.2 parts by mass of a leveling agent, with a total non-volatile content of 100 parts by mass.
5. The composite aluminum-plastic film for batteries based on electron beam curing according to claim 1, characterized in that, The resin side coating is formed of 73.8 parts by mass of second polycarbonate polyurethane acrylate, 18.0 parts by mass of first polycarbonate polyurethane acrylate, 8.0 parts by mass of tricyclodecanediethanol diacrylate and 0.2 parts by mass of leveling agent, with a total non-volatile content of 100 parts by mass.
6. The composite aluminum-plastic film for batteries based on electron beam curing according to claim 1, characterized in that, The biaxially oriented polyamide film has a thickness of 25.0 μm, the aluminum foil has a thickness of 40.0 μm, the bonding layer is a maleic anhydride-grafted polypropylene layer with a thickness of 5.0 μm, and the heat-sealing layer is a cast polypropylene layer with a thickness of 65.0 μm.
7. The composite aluminum-plastic film for batteries based on electron beam curing according to claim 1, characterized in that, The side of the aluminum foil facing the gradient interface bonding layer has a chromium-free conversion film, the weight gain of the chromium-free conversion film is 15 mg / m 2 .
8. The composite aluminum-plastic film for batteries based on electron beam curing according to claim 1, characterized in that, The non-volatile content of the gradient interfacial adhesive layer is 4.50 g / m 2 .
9. The composite aluminum-plastic film for batteries based on electron beam curing according to claim 1, characterized in that, The gradient interface adhesive layer is formed by electron beam curing of a metal side coating first formed on the surface of the aluminum foil and a resin side coating subsequently formed on the metal side coating, with the electron beam irradiating from one side of the biaxially oriented polyamide film.
10. A method for preparing a composite aluminum-plastic film for batteries based on electron beam curing according to any one of claims 1-9, characterized in that, The process includes the following steps: preparing the first polycarbonate polyurethane acrylate and the second polycarbonate polyurethane acrylate; preparing a metal side coating liquid and a resin side coating liquid; first coating the aluminum foil to be coated with the metal side coating liquid, so that the residual solvent of the first coating film is 8.6%-17.2%; after the first coating film leaves the flash evaporation section, coating the resin side coating liquid after 1.8-4.5s, and then drying them together; after the biaxially oriented polyamide film is combined with the resin side coating film, electron beam irradiation is performed from one side of the biaxially oriented polyamide film, the electron beam accelerating voltage is 150-170keV, and the planar absorbed dose of the adhesive layer is 28.0-36.0kGy.
Citation Information
Patent Citations
Lithium cell packaging film and polyurethane adhesive therefor
CN101914363B
Aluminum-plastic packaging film for lithium-ion batteries and its manufacturing method
CN102602597B
An electron beam cured composite adhesive, a flexible packaging composite film, and their preparation method
CN110387208B
